'Essentially it's just a lot of bedrooms': architectural design, prescribed personalisation and the construction of care homes for later life. Issue 7 (27th April 2018) - Nettleton, Sarah; Buse, Christina; Martin, Daryl
Abstract: This article draws on ethnographic data from a UK Economic and Social Research Council (ESRC) funded study called ' Buildings in the Making' . The project aims to open up the black box of architectural work to explore what happens between the commissioning of architectural projects through to the construction of buildings, and seeks to understand how ideas about care for later life are operationalised into designs. Drawing on recent scholarship on 'materialities of care' and 'practising architectures', which emphasise the salience of material objects for understanding the politics and practices of care, we focus here on 'beds'. References to 'beds' were ubiquitous throughout our data, and we analyse their varied uses and imaginaries as a 'way in' to understanding the embedded nature of architectural work. Four themes emerged: 'commissioning architectures and the commodification of beds'; 'adjusting architectures and socio‐spatial inequalities of beds'; 'prescribing architectures and person‐centred care beds'; and 'phenomenological architectures and inhabiting beds'. We offer the concept prescribed personalisation to capture how practising architectures come to reconcile the multiple tensions of commodification and the codification of person centred care, in ways that might mitigate phenomenological and serendipitous qualities of life and living in care settings during later life.